The properties of gases and liquids - Elliott, J. Richard; Diky, Vladimir; Knotts, Thomas A.; Wilding, W. Vincent (New York McGraw-Hill, 2023)
"Fully updated for the latest advances, this must-have chemical engineering guide serves as a single source for up-to-date physical data, chemical data, and predictive and estimation methods. The Properties of Gases and Liquids, Sixth Edition provides the latest curated data on over 480 compounds and includes a special section devoted to the interpretation of uncertainty in physical property estimation. You will get new coverage of advanced EOSs with correlated and predicted parameters, advanced computational methods, quantum density functional theory, and semi-empirical combinations. Clear explanations and sample calculations are provided throughout this all-inclusive resource."
Electronic reproduction
Keywords: Gases; Liquids; Electronic books